Peningkatan Kemampuan Membaca Kitab Kuning dengan Metode Sorogan pada Santri Pondok Pesantren Walisongo - Hidayah, Ridho (LP3M STAI Ibnurusyd, 2022)
In this study, the main problem that must be faced is how we can improve the ability of students to read the yellow book. The yellow book or what we often call the bald book has messages that are so valuable that they require special skills to understand them. The ability to read the yellow book is one of the most important factors to understand the content contained in the text of the book. This ability is very necessary called habituation, and training, training to read the yellow book is one of the efforts to improve the ability of students to understand the yellow book. This sorogan training is a form of community service carried out by the Asatidz Council at MDF Walisongo Islamic Boarding School. Where a teacher will teach the values contained in the yellow book. In learning the yellow book, the walisongo Islamic boarding school uses the sorogan method, where the students come forward one by one to face the kiyai or ustadz, then read the book by paying attention to the nahwu and shorofnya. Then after reading, the students then translate and explain the contents of the book. The sorogan method aims so that students can read the yellow book properly and correctly according to the nahwu and shorof rules, and can understand the contents in a yellow book. This research was conducted to find out how to increase the ability to read the yellow book with the sorogan method at the walisongo Islamic boarding school. The sorogan method is one of the traditional methods applied at the Walisongo Islamic Boarding School to assist students in reading and understanding the Yellow Book. The results of this study illustrate that the Walisongo Islamic Boarding School has given birth to a number of students who are able to read books with the initial stage knowing sakal, the second stage knowing Arabic grammar, and the third stage being able to provide the real meaning contained in the book being read.